2012
DOI: 10.1021/ef201758g
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Studies on the Adsorption/Occlusion Phenomena Inside the Macromolecular Structures of Asphaltenes

Abstract: Asphaltenes are the polar macromolecules with complex structures in oils, usually existing as aggregates. Inside the macromolecular structures of asphaltenes, some other fractions can be adsorbed/occluded, and the occluded compounds contain some important geochemical information. However, the adsorption/occlusion phenomena of asphaltenes need verification. Thus, this work was aimed to experimentally study the adsorption/occlusion processes inside the asphaltenes, using the deuterated paraffin n-C 20 D 42 as th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 25 publications
(53 reference statements)
0
19
0
Order By: Relevance
“…Experimental evidence of the fractal-type structure of asphaltene aggregates suggest they could adsorb or trap other compounds from oils (Carbognani and Rogel, 2002;Liao et al, 2005;Liao et al, 2006;Yang et al, 2009;Zhao et al, 2012;Derakhshesh et al, 2013). These occluded compounds contain important geochemical information (Yang et al, 2009) about the aging and origin of the crude oil.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental evidence of the fractal-type structure of asphaltene aggregates suggest they could adsorb or trap other compounds from oils (Carbognani and Rogel, 2002;Liao et al, 2005;Liao et al, 2006;Yang et al, 2009;Zhao et al, 2012;Derakhshesh et al, 2013). These occluded compounds contain important geochemical information (Yang et al, 2009) about the aging and origin of the crude oil.…”
Section: Introductionmentioning
confidence: 99%
“…However, recent studies have shown that a series of even carbon numbered n-alk-1-enes are present in the trapped fractions of asphaltenes (Yang et al, 2009;Zhao et al, 2010Zhao et al, , 2012Tian et al, 2012) and solid bitumens (Cheng et al, 2012(Cheng et al, , 2013. They may be stable in these geomacromolecules owing to the protection afforded by the matrix, which inhibits transformation of the trapped n-alk-1-enes during later geochemical processes.…”
Section: Introductionmentioning
confidence: 99%
“…This may be due to the presence of mobile petroporphyrins additional to the occluded petroporphyrins in the structure of asphaltenes generated by the action of the temperature on the samples in the vacuum towers. , Interaction of different compounds with asphaltenes and their aggregates is an interesting phenomenon, which is relevant to properties such as swelling and solvent interaction. This effect has been studied by several authors and the nature of the interaction still in discussion. The adsorption and occlusion of different compounds in asphaltenes aggregates have been studied by Castillo et al; they proposed the existence of two mechanisms for trapping these molecules: occlusion and adsorption onto aggregates with the occlusion as the predominant effect …”
Section: Materials and Methodsmentioning
confidence: 99%